Interpretation of obstruction of justice in the crime of corruption in law number 31 year 1999 - Permai Yudi; Herry Anto Simanjuntak (The International Journal of Politics and Sociology Research, 2023)
If we look at Article 21 of Law No. 31/1999 on the Eradication of Corruption, there is no explicit definition of the act of "preventing, hindering or thwarting directly or indirectly", which raises the possibility of misinterpretation. Such errors include categorisation of the act, timing, and misinterpretation of the general legal norm. In terms of how the norm can be applied, it is necessary to understand the content of the legal norm as a whole regarding the meaning of each act in the provision. Thus, it will be clear about how the criminal act is carried out and can be categorised as a criminal act that fulfils all the elements in the provisions of Article 21 of Law No. 31 of 1999. This study is a normative study, with a statutory approach. Other approaches, namely existing conceptual and case approaches, will also be used to provide perspective in this study.  The results of the study are manifested in the form of all acts that prevent, obstruct and thwart directly and indirectly, by not requiring the existence of consequences arising from these acts, namely being prevented, obstructed or thwarted an investigation, prosecution and trial examination carried out, but it is enough to prevent, obstruct and thwart according to his knowledge, the act can obstruct or thwart an investigation, prosecution and trial examination then the act is considered final.